Overturning certainties in Near Eastern archaeology : a festschrift in honor of K. Aslihan Yener - Yener, K. Aslihan.; Maner, Çiğdem.; Horowitz, Mara T., 1976-; Gilbert, Allan S., 1948- (Culture and History of the Ancient Near East, 2017)
This volume, Overturning Certainties in Near Eastern Archaeology , is a festschrift dedicated to Professor K. Aslıhan Yener in honor of over four decades of exemplary research, teaching, fieldwork, and publication. The thirty-five chapters presented by her colleagues includes a broad, interdisciplinary range of studies in archaeology, archaeometry, art history, and epigraphy of the Ancient Near East, especially reflecting Prof Yener's interests in metallurgy, small finds, trade, Anatolia, and the site of Tell Atchana/Alalakh.